Prophylactic Use of Fluconazole in Very Premature Infants - Zhang, Deshuang; Xie, Dongke; He, Na; Wang, Xiaoling; Dong, Wenbin; Lei, Xiaoping (Frontiers in Pediatrics, 2021)
Objective: To evaluate the efficacy, safety, and fungal sensitivity of prophylactic fluconazole use in very premature infants. Methods: We performed a retrospective historical comparative analysis of 196 very premature in-fants (113 in the prophylaxis group and 83 in the rescue group). The incidence of nosocomial fungal infection (NCFI) and pathogenic fungi, their drug sensitivity, and the minimum inhibitory concen-tration (MIC) of fluconazole were compared between the two groups. We also analyzed differences in short-term adverse outcomes, such as drug-induced liver or renal function disruption, fungal-attributable death, bronchopulmonary dysplasia (BPD), retinopathy of prematurity (ROP), periventricular leukomalacia (PVL), intraventricular hemorrhage (IVH), and necrotizing enterocol-itis (NEC), between the groups. The effects of the prophylactic fluconazole strategy on NCFI and short-term adverse outcomes were assessed by multivariate logistic regression. Results: Candida albicans (46.7%) and Candida glabrata (43.3%) were the main culprit pathogens causing NCFI. The incidence of NCFI was significantly lower in the prophylaxis group than in the rescue group (15.9% vs. 45.8%, P<0.001). However, fewer fungi were completely sensitive to flu-conazole (40% vs. 85%, P<0.05) and the MIC of fluconazole was higher (16.0 [3.5~16.0] µg/ml vs. 3.0 [1.0~8.0] µg/ml, P<0.001) in the prophylaxis group than in the rescue group. Compared with the rescue group, the prophylaxis group had a lower risk of NCFI (adjusted OR 0.25; 95% CI 0.11, 0.55). Additionally, the prophylaxis group had significantly lower risks of combined outcomes (one or more complications, such as BPD, ROP needing interventions, PVL and IVH grade >2, NEC stage ≥2, and fungal-attributable death) (adjusted OR 0.44; 95% CI 0.21, 0.92). There was no significant difference in serum alanine transferase (ALT), aspartate transaminase (AST), creatinine (Cr), or direct bilirubin (DBIL) levels between the two groups. Conclusions: Fluconazole prophylaxis reduced NCFI and improved combined clinical outcomes in very premature infants, with no increased risks of serious short-term adverse side effects; however, the MIC of fluconazole showed significant increases. Therefore, further optimization of preventive strategies is necessary to maintain the sensitivity of fluconazole against fungal isolates.